2011
DOI: 10.1177/2042018811423770
|View full text |Cite
|
Sign up to set email alerts
|

Serum adiponectin and resistin in relation to insulin resistance and markers of hyperandrogenism in lean and obese women with polycystic ovary syndrome

Abstract: Abstract:Objective: The role of insulin resistance in polycystic ovary syndrome (PCOS) has been established. However the role of adiponectin and resistin in the relationship between insulin resistance as markers of obesity and PCOS has not been conclusive. This study aims to determine the influence of the serum levels of adiponectin and resistin on PCOS, and assess possible correlations with the hormonal and metabolic parameters of the syndrome and obesity. Methods: This study continued a case control study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
4
18
1
Order By: Relevance
“…As mentioned, in the present investigation it was found that serum adiponectin levels were lower in obese PCOS patients compared to lean and obese women without PCOS, in addition to altered parameters of insulin resistance (HOMA and ISI Com posite) and higher FAI values in the obese PCOS group. These results are in agreement with previous reports, which estab lished that BMI, IR, and FAI make a highly significant contribu tion to adiponectin levels in PCOS [38]. The link between FAI, IR and adiponectin levels may exist for several reasons.…”
supporting
confidence: 93%
“…As mentioned, in the present investigation it was found that serum adiponectin levels were lower in obese PCOS patients compared to lean and obese women without PCOS, in addition to altered parameters of insulin resistance (HOMA and ISI Com posite) and higher FAI values in the obese PCOS group. These results are in agreement with previous reports, which estab lished that BMI, IR, and FAI make a highly significant contribu tion to adiponectin levels in PCOS [38]. The link between FAI, IR and adiponectin levels may exist for several reasons.…”
supporting
confidence: 93%
“…It has been suggested that resistin may have a local paracrine action in the regulation of insulin resistance in obesity and PCOS [35]. However, blood resistin levels were similar among obese and non-obese women with PCOS [26,36]. It seems that resistin is not a major mediator of obesity effects on PCOS phenotype.…”
Section: Resistinmentioning
confidence: 65%
“…Although measuring IR with dynamic methods seems to be accurate but inconvenient for clinical practice in PCOS patients, HOMA-IR can be used as a surrogate measure of IR. In this context, elevated HOMA-IR scores in PCOS patients have been described in a number of studies (21)(22)(23)(24). In one of the largest of these studies, which included 271 PCOS patients, the prevelance of IR was found to be 64% according to the HOMA-IR measurement (21).…”
Section: Discussionmentioning
confidence: 97%